Analisis Pengaruh Knowlegde Management System terhadap Kinerja Karyawan PT. Global Infotech Solution - Zevanya Martha Haurissa; Agustinus Fritz Wijaya (Jurnal Ilmiah Terpadu Universitas Bina Darma, 2020)
The application of knowlegde management can benefits to the company and improving employee performance. The application of knowlegde management has been recognized as an important instrument for achieving the specific objectives of corporate organizations and so as to maintain economic growth and competitive advantage. The purpose of this study is to examine the effect of knowledge management systems on employee performance at PT Global Infotech Solution. This type of research that is explanatory research with a quantitative approach. Researchers used this sampling technique because the total population of 55 respondents. To conduct data analysis, data processing is carried out using path analysis. The results showed that organizational support significantly influenced employee performance. In addition to organizational support factors, knowledge management factors also have a significant impact on employee performance. Knowledge management is influenced by the support of corporate organizations. Knowledge management interventions in improving employee performance obtained significant results, so companies can use knowledge management systems that can improve employee performance. Companies can use knowledge management as a major element in the management of strategies and processes. The main indicator in developing knowledge management is an innovative corporate culture and always able to adapt to technological developments is the main key.